2021
DOI: 10.1007/s00158-021-03081-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of topology and layout of modular stiffeners on shells and plates

Abstract: Stiffened shells and plates are widely used in engineering. Their performance is highly influenced by the arrangement, or layout, of stiffeners on the base shell or plate and the geometric features, or topology, of these stiffeners. Moreover, modular design is beneficial, since it allows for increased quality control and mass production. In this work, a method is developed that simultaneously optimizes the topology of stiffeners and their layout on a base shell or plate. This is accomplished by introducing a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results showed that the performance of the optimized machine was improved to different degrees and that the beam mass was reduced by 2.1%. Bakker C et al [ 21 ] proposed a method for optimizing the stiffened plate and its structural layout to improve the performance of the stiffened plate shell. Jiang Shufeng et al [ 22 ] designed and researched the DVT250 machine tool crossbeam, and their results show that the diamond rib plate structure, as the optimized crossbeam structure, has the best lightweight effect.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the performance of the optimized machine was improved to different degrees and that the beam mass was reduced by 2.1%. Bakker C et al [ 21 ] proposed a method for optimizing the stiffened plate and its structural layout to improve the performance of the stiffened plate shell. Jiang Shufeng et al [ 22 ] designed and researched the DVT250 machine tool crossbeam, and their results show that the diamond rib plate structure, as the optimized crossbeam structure, has the best lightweight effect.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this framework, Feng et al [36] effectively utilized B-spline control parameters to characterize the stiffener distribution reinforcing the plate/shell structures. Some other latest investigations conducted on the stiffener optimization of plate structures can be referred to [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%